Rabočij klass stran Azii i Afriki. Spravočnik. [Pri učast. L.A. Avdjuninoj, M.M. Avseneva, V.G. Arkad'eva i dr. Pod red. A.A. Iskenderova, V.I. Kiseleva, I.V. Milovanovȧ i dr.] (Nauka, 1964)
AN SSSR. Institut narodov Azii. Institut Afriki.